Mechanism of administrative decision making by a state higher educational institution on the basis of analysis results - Ковнір, Д. А. (Scientific Progress & Innovations, 2016)
The author’s own definition of the concept «managerial decision» is offered in the article, the model of decision making through analyzing the levels of performance indicators of the financial mechanism of state higher institution has been created and the complex system of typical model administrative decision making by a state higher educational institution on the basis of analysis results has been developed. The recommendations on administrative decision making according to the analysis results of economic activity have been provided.